Girl with Death Mask - Givhan, Jennifer (Blue light books., 2018)
Love, tequila, sex, first periods, late nights, abuse, and heartache. The journey from girl to womanhood is brimming with transformative magic that heals even as it shatters. These are the memories that haunt the dreams of what was and what could have been in Girl with Death Mask. In four rich and imaginative movements of poems, Jennifer Givhan profiles the suffering and the love of a Latina girl and then mother coming to terms with sexual trauma. Her daughter is a touchstone of healing as she seeks to unravel her own emotions and protect the next generation of women with a fierceness she must find within. Givhan exploits changing poetic forms to expose what it means to mature in a female body swirling with tenderness, violence, and potential in an uncertain world. Girl with Death Mask is a cathartic and gripping confession of the trials of adolescence and womanhood.